2022
DOI: 10.1155/2022/9072508
|View full text |Cite
|
Sign up to set email alerts
|

Biosynthesis and Characterization of Silver Nanoparticles Produced by Phormidium ambiguum and Desertifilum tharense Cyanobacteria

Abstract: The world faces a challenge with the pervasion of multidrug-resistant bacteria that encourages scientists to develop and discover alternative, ecofriendly, and easy-to-produce new antibacterial agents. Our work is part of the greater effort of scientists around the world to achieve this goal by the biological synthesis of silver nanoparticles using cyanobacterial extracellular and intracellular components as nonchemical reducing agents. Two Egyptian cyanobacteria were isolated and identified according to 16S r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 54 publications
2
30
0
Order By: Relevance
“…The authors reported that the small size and crystalline nature of Ag-NPs was a significant factor in enhancing the antioxidant activity of NPs. Hanna et al screened the antioxidant potential of Ag-NPs produced by Desertifilum tharense and Phormidium ambiguum (D-Ag-NPs and P-Ag-NPs, respectively) and algal extracts using DPPH assays [ 43 ]. D-Ag-NPs and P-Ag-NPs exhibited a scavenging activity of 43.75% and 48.7%, respectively, while that of D. tharense and P. ambiguum was 36.14% and 33.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors reported that the small size and crystalline nature of Ag-NPs was a significant factor in enhancing the antioxidant activity of NPs. Hanna et al screened the antioxidant potential of Ag-NPs produced by Desertifilum tharense and Phormidium ambiguum (D-Ag-NPs and P-Ag-NPs, respectively) and algal extracts using DPPH assays [ 43 ]. D-Ag-NPs and P-Ag-NPs exhibited a scavenging activity of 43.75% and 48.7%, respectively, while that of D. tharense and P. ambiguum was 36.14% and 33.9%, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…The antioxidant activity of C@Ag-NPs and aqueous algal extract was examined using a DPPH assay according to the method described by Hanna et al [ 43 ]. Briefly, 1 mg/mL C@Ag-NPs was sonicated for 10 min and then various concentrations of NPs (1000, 500, 250, 125, 62.5, 31.25, 15.6, 7.8, 3.9, and 1.95 µg/mL) were prepared.…”
Section: Methodsmentioning
confidence: 99%
“…A phase-contrast microscope and a digital camera were used to take microphotographs of each species (Olympus SC180). Morphological identification: By the following existing literature, the morphological traits of specimens of cyanobacterial species were identified and enumerated (Behera et al, 2020;Behera et al, 2021;Bhakta et al, 2015;Bhakta et al, 2014;Das and Adhikary, 2014;Dash et al, 2020;Dash et al, 2021;Desikachary, 1959;Hanna et al, 2022;Hindák, 1977;Jena et al, 2006;Khaybullina et al, 2010;Kim and Lee, 2014;Komárek, 2005;Komárek and Anagnostidis, 1999;Komárek et al, 1983;Komárek and Johansen, 2015;Komárek et al, 2011;Komárek et al, 2013;Komárková et al, 2010;Lopez-Bautista et al, 2007;Loza et al, 2013;Maharana et al, 2019;Mahendra Perumal and Anand, 2009;Nakano and Isagi, 1987;Škaloud, 2008, 2010;Pradhan et al, 2021a;Pradhan et al, 2021b;Stace et al 2005;Vijayan and Ray, 2015;West et al, 1912).…”
Section: S73mentioning
confidence: 99%
“…The researchers suggest nitrate reductase stimulates the enzyme synthesizing nanosilver particles in Bacillus licheniformis. Other studies have shown that nitrogenases (nitrogen-fixing enzymes) can convert gold ions into gold nanoparticles as powerful reducing agents (Hanna et al, 2022).…”
Section: Nanoparticle Intracellular Synthesismentioning
confidence: 99%
“…Cyanobacteria are decent biological systems for the synthesis of intracellular and extracellular ATP. Spirulina can synthesize monometallic and bimetal nanoparticles of gold, silver, and gold-silver extracellularly (Hanna et al, 2022).…”
Section: Function and Involvement Of Cyanobacteria In Nanoparticle Sy...mentioning
confidence: 99%